Transcriptomic and Metabolomic Profiling Reveals That KguR Broadly Impacts the Physiology of Uropathogenic Escherichia coli Under in vivo Relevant Conditions - Yang, Dawei; Jiang, Fengwei; Huang, Xinxin; Li, Ganwu; Cai, Wentong (Frontiers in Microbiology, 2021)
Urinary tract infections are primarily caused by uropathogenic Escherichia coli (UPEC). In contrast to the intestinal E. coli strains that reside in nutrient-rich gut environment, UPEC encounter distinct niches, for instance human urine, which is an oxygen- and nutrient-limited environment. Alpha-ketoglutarate (KG) is an abundant metabolite in renal proximal tubule cells; and previously we showed that two-component signaling system (TCS) KguS/KguR contributes to UPEC colonization of murine urinary tract by promoting the utilization of KG as a carbon source under anaerobic conditions. However, knowledge about the KguR regulon and its impact on UPEC fitness is lacking. In this work, we analyzed transcriptomic and metabolomic changes caused by kguR deletion under anaerobiosis when KG is present. Our results indicated that 620 genes were differentially expressed in the ΔkguR mutant, as compared to the wild type; of these genes, 513 genes were downregulated and 107 genes were upregulated. Genes with substantial changes in expression involve KG utilization, acid resistance, iron uptake, amino acid metabolism, capsule biosynthesis, sulfur metabolism, among others. In line with the transcriptomics data, several amino acids (glutamate, lysine, etc.) and uridine 5′-diphosphogalactose (involved in capsule biosynthesis) were significantly less abundant in the ΔkguR mutant. We then confirmed that the ΔkguR mutant, indeed, was more sensitive to acid stress than the wild type, presumably due to downregulation of genes belonging to the glutamate-dependent acid resistance system. Furthermore, using gene expression and electrophoretic mobility shift assays (EMSAs), we demonstrate that KguR autoregulates its own expression by binding to the kguSR promoter region. Lastly, we performed a genome-wide search of KguR binding sites, and this search yielded an output of at least 22 potential binding sites. Taken together, our data establish that in the presence of KG, KguR broadly impacts the physiology of UPEC under anaerobiosis. These findings greatly further our understanding of KguS/KguR system as well as UPEC pathobiology.